Reduced Maximum Pitch Elevation Predicts Silent Aspiration of Small Liquid Volumes in Stroke Patients - Rajappa, Akila Theyyar; Soriano, Kristie R.; Ziemer, Courtney; Troche, Michelle S.; Malandraki, Jaime Bauer; Malandraki, Georgia A. (Frontiers in Neurology, 2017)
Background and Purpose: Preliminary evidence has shown that reduced ability to maximally raise vocal pitch correlates with the occurrence of aspiration (i.e. airway invasion by food or liquid). However, it is unclear if this simple task can be used as a reliable predictor of aspiration in stroke patients. Our aim was to examine whether maximum vocal pitch elevation predicted airway invasion and dysphagia in stroke. Methods: Forty-five consecutive stroke patients (< 1 month post-stroke) at a rehabilitation setting participated in a videofluoroscopic swallow study and two maximum vocal pitch elevation tasks. Maximum pitch was evaluated acoustically (Max F0) and perceptually. Swallowing safety was rated using the Penetration/Aspiration Scale (PAS) and swallowing performance was assessed using components of the Modified Barium Swallow Impairment Profile (MBSImP). Data were analyzed using simple regression and receiver operating characteristics curves to test the sensitivity and specificity of Max F0 in predicting aspiration. Correlations between Max F0 and MBSImP variables were also examined. Results: Max F0 predicted silent aspiration of small liquid volumes with 80% sensitivity and 65% specificity (p=0.023; AUC: 0.815; cut off value of 359.03 Hz). Max F0 did not predict non-silent aspiration or penetration in this sample and did not significantly correlate with MBSImP variables. Furthermore, all participants (11% of sample) who aspirated silently on small liquid volumes had suffered cortical or subcortical lesions. Conclusion: In stroke patients (< 1 month post-stroke) reduced maximum pitch elevation predicts silent aspiration of small liquid volumes with high sensitivity and moderate specificity. Future large-scale studies focusing on further validating this finding and exploring the value of this simple and noninvasive tool as part of a dysphagia screening are warranted.